HIGHER EDUCATION IN ONLINE ENVIRONMENT - CHALLENGES AND POSSIBLE SOLUTIONS - Luminiţa Mihaela DRĂGHICESCU; Ioana STĂNCESCU (National Centre for Policy and Evaluation in Education, 2021)
In the current national and international context, the education "hosted" in the online environment, which was once only a secondary solution, rarely used, has become the main way to ensure the continuity of the learning process. In this study, we aimed to capture the reactions of those who were the first to experiment an exclusively online, learning process, i.e. the reactions of the students. We used an investigative approach focused on the following objectives: identifying the perception of students/learners regarding the efficiency and quality of the educational process carried out in the online environment and highlighting ways to improve teaching activities conducted online. The main research method was the questionnaire-based survey. The questionnaire was administered online, integrating a series of items that addressed issues such as: students' participation in educational activities, problems encountered, solutions to optimize the didactic process conducted in the online environment. Following the investigative approach, the main conclusions are the following: most of the surveyed students consider that the educational activities carried out in the online environment do not have the same efficiency as the direct activities (face to face); the main problems highlighted by the respondents were: overload, fatigue, demotivation, learning difficulties in understanding and operating with certain content, poor Internet connection, but also the lack of necessary indications to facilitate learning. We appreciate that the results of our study may be relevant for practitioners in the field of education, especially for those from higher education, but also for all those interested in digital education.